Edukasi Hukum Dampak Negatif Judi Online Bagi Siswa di Kota Palangka Raya: Legal Education on the Negative Impact of Online Gambling for Students in Palangka Raya City - Fransisco, Fransisco; Wardhani, Novea Elysa; Evi, Evi; Sudiarti, Elin; Dewi, Yurika Fahliany (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2025)
Gambling is a game requiring players to have money or objects used as bets. Along with its development in the current digital era, gambling has also undergone development. The phenomenon of online gambling today also penetrates teenagers, especially students. The phenomenon of online gambling is one of the deviant behaviors that hurts students' psychological conditions, academic achievements, and social conditions. Therefore, the community service activities at Nurul Ihsan Islamic High School, Palangka Raya, are very relevant to online gambling, which is currently developing among teenagers, especially students. This activity was carried out to provide education about the negative impact of online gambling that can affect the psychological condition of students. Various aspects related to online gambling were explained, such as the form of online gambling, the negative impact of online gambling, and the legal consequences for online gambling perpetrators. This activity also provides prevention strategies that can be done to avoid online gambling practices for students, as well as handling strategies for students who have fallen into online gambling. A total of 50 Nurul Ihsan Islamic High School students were followed by receiving material related to the negative impact of online gambling from a legal perspective. Furthermore, the activity was closed with an evaluation, namely questions and answers, and the provision of post-tests. The results of the activity provided information to increase knowledge and understanding of the negative impact of online gambling for students from a legal perspective, as well as efforts to prevent online gambling practices among students.